A comparative study of liver function test between normal neonates and neonates with different stages of hypoxic ischemic encephalopathy in a district medical college of Eastern India - Kanai Lal Barik; Barnika Purkayastha; Nilanjan Ghosh; Laha, Sumanta; Amit Adhikary; Sayan Bera (Asian Journal of Medical Sciences, 2022)
Background: Hepatic dysfunction is a known complication in neonates with hypoxic ischemic encephalopathy (HIE). Aims and Objectives: We conducted this study to compare hepatic function between normal and asphyxiated newborn and whether the changes in liver function vary with the grade of HIE. Materials and Methods: This observational analytical cross-sectional study was done in a rural medical college of eastern India for 1 year with 51 HIE (17 each in HIE I, II, and III group) and 51 healthy neonates as control. Biochemical parameters of liver function such as alanine transferase (ALT), aspartate transferase (AST), alkaline phosphatase (ALP), total serum bilirubin (TSB), serum albumin, and prothrombin time (PT) were measured in both groups between 48 and 72 h of birth. Results: We found that TSB, liver enzymes, and PT ware significantly elevated and serum albumin reduced in HIE group in comparison to control group. However, TSB, PT, and serum albumin does not differ much among three stages of HIE. By contrast, liver enzymes increases significantly among three stages of HIE, and also, there is significant difference in ALT, AST, and ALP between survivor and non-survivor of HIE babies. Conclusion: Hence, liver function test may serve as an useful early marker of perinatal asphyxia when the history of birth asphyxia is lacking and it can also be used as a prognostic indicator as there is more rise of liver enzymes from low to high grade of HIE and from survived to expired HIE babies.